Problems in the implementation of the APTTA Agreement and Recommendations for its Future - Stanikzai, Amin (Technium Social Sciences Journal, 2022)
In this research article, you will read that both parties of the agreement, Afghanistan and Pakistan, believe that good relations between the two countries can be a means of resolving many issues, including trade and transit. Afghan businessmen, government officials and general people as well as the Pakistanis hope that good relations with each other will resolve the problems of Afghan and Pakistani businessmen and will benefit people of both countries. Trade and transit problems can be solved by strengthening the bilateral relations. The problems of implementation of the APTTA Agreement are resolvable and there will be no grievances if both parties show commitment and mutual respect. Both parties accept the availability of the problems; however, each party is keen in resolving these issues on its own advantages, which complicates the implementation of the APTTA agreement. In this research article, we have tried to dig out relevant issues of Afghan and Pakistan transit and trade in accordance to the agreed terms of the APTTA agreement, concord with the regional conditions to find out the problems of Afghan and Pakistani traders and to re-sign the agreement keeping in view the suggestions from both parties with strong will so that the mentioned agreement brings prosperity and welfare to the people of the region as a whole, particularly of South and Central Asia. Both Afghan and Pakistani hope to include other countries in the agreement in the future. Afghanistan has demanded the inclusion of India and Pakistan has demanded the inclusion of Central Asian countries, especially Tajikistan. To understand the terms, used in this article, are explained in detail under a separate heading in the coming pages.